Speech comprehension in noisy environments: Evidence from the predictability effects on the N400 and LPC - Hsin, Cheng-Hung; Chao, Pei-Chun; Lee, Chia-Ying (Frontiers in Psychology, 2023)
Speech comprehension involves context-based lexical predictions for efficient semantic integration. This study investigated how noise affects the predictability effect on event-related potentials (ERPs) such as the N400 and late positive component (LPC) in speech comprehension. Twenty-seven listeners were asked to comprehend sentences in clear and noisy conditions (hereinafter referred to as “clear speech” and “noisy speech,” respectively) that ended with a high- or low-predictability word during electroencephalogram (EEG) recordings. The study results regarding clear speech showed the predictability effect on the N400, wherein low-predictability words elicited a larger N400 amplitude than did high-predictability words in the centroparietal and frontocentral regions. Noisy speech showed a reduced and delayed predictability effect on the N400 in the centroparietal regions. Additionally, noisy speech showed a predictability effect on the LPC in the centroparietal regions. These findings suggest that listeners achieve comprehension outcomes through different neural mechanisms according to listening conditions. Noisy speech may be comprehended with a second-pass process that possibly functions to recover the phonological form of degraded speech through phonetic reanalysis or repair, thus compensating for decreased predictive efficiency.